Implementation of Access by KAI Innovation in Public Service Transformation at PT KAI (Persero) Regional Division II West Sumatra - Frizni, Dinda; Adnan, M. Fachri (Indonesian Journal Publisher, 2024)
This study is based on the changes in services that PT KAI (Persero) made when KAI launched the Access application, which serves as a tool to provide customers with train ticket purchasing services. The purpose of this study is to determine how effectively the Access innovation by KAI is being used, as well as the obstacles faced in its implementation. This type of research is qualitative, and the method is descriptive. Data was collected through documentation studies and interviews. Source triangulation techniques and data analysis techniques were used to test the validity of the data; both techniques involved data preparation, inference, and reduction. The research findings show that this KAI access innovation has been quite helpful to passengers with some additional features, and this innovation has changed the service significantly. However, there are still problems with unclear seat information and applications.